The Development of Lithium Ion Recovery Method by Activated Carbon and Natural Zeolite-based Adsorbent - Chandra Wahyu Purnomo; Endhy Kesuma; Sang Kompiang Wirawan; Hirofumi Hinode (ASEAN Journal of Chemical Engineering, 2019)
Coconut shell char and natural zeolite been activated and then tested to separate between lithium and cobalt ions in solutions. The capacity of adsorption and selectivity between the ions were investigated. The longer adsorption time, the capacity was getting better but the selectivity decreased. It was observed that the optimum selectivity was obtained by 3 hours adsorption using activated carbon. The chemical activated sample has superior performance and selectivity compared with physical activation carbons of the same activation temperature. After the adsorption, pure lithium solution can be obtained while the other metal is adsorbed inside the adsorbent